1984
DOI: 10.1021/ja00314a051
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis of 3-chlorodiazirine in the presence of alkenes. Kinetic evidence for intervention of a carbene-alkene intermediate in addition of chlorocarbene to alkene

Abstract: During the course of the studies on the competition between intramolecular 1,2-H shift and intermolecular addition of benzylchlorocarbene to alkene, we obtained chemical evidence for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 3 publications
3
26
0
Order By: Relevance
“…We found that favorable interaction energy contributes to negative ∆E at intermediate separation of the carbenes and alkenes studied here and suggests the formation of carbene-alkene precursor complexes, although the existence of these has been debated in the literature. [20][21][22][23][24][25][26][27][28][29] We have confirmed π-complexes for cycloadditions to 2a, 2b, and 2d that are stabilized by 0-5 kcal mol…”
Section: Resultsmentioning
confidence: 56%
“…We found that favorable interaction energy contributes to negative ∆E at intermediate separation of the carbenes and alkenes studied here and suggests the formation of carbene-alkene precursor complexes, although the existence of these has been debated in the literature. [20][21][22][23][24][25][26][27][28][29] We have confirmed π-complexes for cycloadditions to 2a, 2b, and 2d that are stabilized by 0-5 kcal mol…”
Section: Resultsmentioning
confidence: 56%
“…If 56 was the only intermediate, the ratio 59/ 58 would increase linearly with the concentration of alkene. However, curved plots were obtained on photolysis of 54, [80] as shown for 54a Ϫ TME in Figure 1. The curvature Scheme 13.…”
Section: Alkenesmentioning
confidence: 98%
“…Liu and Bonneau assigned this role to CAC 57, [80][81] while rearrangement in the excited state (RIES) of the diazirine (1,2-H shift in concert with extrusion of nitrogen) was advocated by Goodman, [82] Platz, [83] and Moss.…”
Section: Alkenesmentioning
confidence: 99%
“…Even more difficult, because the interaction energies should be smaller, is the modulation of carbenic reactivity by intermediate carbene−π electron complexation. Liu and Bonneau maintain that the transient formation of carbene−alkene π-complexes is integral to the competition between intramolecular rearrangement (Re) and intermolecular addition (Ad) when alkylhalocarbenes are generated in the presence of alkenes. , However, Houk's calculations suggest that additions of chlorocarbenes to ethylene or tetramethylethylene (TME) proceed to cyclopropanes without transiting bound carbene−alkene complexes. 7a-c Alternatively, broad shallow wells for complexes might occur in the reaction enthalpy profile, but would not constitute minima on the free energy surface 7d. Additionally, Platz and Goodman offer alternative explanations, based on the intervention of excited state carbene precursors, for the kinetic anomalies that originally triggered the suggestion of carbene−alkene complex participation. , …”
mentioning
confidence: 99%